2011
DOI: 10.5489/cuaj.09140
|View full text |Cite
|
Sign up to set email alerts
|

Shock wave lithotripsy in patients requiring anticoagulation or

Abstract: Extracorporeal shockwave lithotripsy (SWL) remains the only truly minimally invasive procedure for the treatment of upper tract nephrolithiasis. Recently, there has been a recent rise in the patients on antiplatelet agents. Therefore, the aim of the present study is to review the literature available regarding SWL in these high-risk patients requiring anti-coagulation therapy. Alternative therapies to SWL are also presented. RésuméLa lithotripsie extracorporelle par ondes de choc (LECOC) demeure la seule inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…Although no randomized studies have been performed to assess the safety of antithrombotic medications in the setting of SWL, there are a number of case reports that demonstrate bleeding complications in these patients [11] , [12] , [13] . In order to decrease the bleeding risk associated with anti-platelet therapy it is necessary to withhold these medications well in advance to the procedure [14] . Attention should be paid to renally excreted medications as patients with stone disease may have renal dysfunction and require a longer wash-out period before reaching a normal coagulation profile.…”
Section: Contraindicationsmentioning
confidence: 99%
“…Although no randomized studies have been performed to assess the safety of antithrombotic medications in the setting of SWL, there are a number of case reports that demonstrate bleeding complications in these patients [11] , [12] , [13] . In order to decrease the bleeding risk associated with anti-platelet therapy it is necessary to withhold these medications well in advance to the procedure [14] . Attention should be paid to renally excreted medications as patients with stone disease may have renal dysfunction and require a longer wash-out period before reaching a normal coagulation profile.…”
Section: Contraindicationsmentioning
confidence: 99%
“…Una contraindicación importante para el uso de las ondas focales es que el paciente esté recibiendo una intensa terapia anticoagulante, 15,36 sobre todo si se deben utilizar altos niveles de energía.…”
Section: Duda: ¿Cuáles Son Sus Contraindicaciones?unclassified
“…Some studies have shown up to a 20-to 40-fold increased risk of peri-renal hematomas and haemorrhagic complications among patients with uncorrected coagulopathies undergoing SWL when compared with patients with a normal bleeding profile, [159][160][161][162] and so in consultation with a haematologist or a cardiologist, bleeding coagulopathies need to be corrected and anticoagulation therapy appropriately withheld around the time of SWL. 163 Patients with an increased risk of thromboembolic disease should be managed by bridging therapy while oral anticoagulation is held.…”
Section: Anti-coagulationmentioning
confidence: 99%